Deformation characteristics of the intermetallic alloy 60NiTi. (March 2017) - Benafan, O.; Garg, A.; Noebe, R.D.; Skorpenske, H.D.; An, K.; Schell, N.
Abstract: The deformation behavior of a Ni-rich Ni55 Ti45 (at.%) alloy, commonly known as 60NiTi (as designated in wt.%), was analyzed using neutron and synchrotron x-ray diffraction during in situ isothermal tension and compression loading, and pre and post-test electron microscopy. The alloy was shown to exhibit remarkable strength and high hardness resulting from a high density of fine Ni4 Ti3 precipitates (size ∼67 nm), which were uniformly dispersed throughout the matrix after a solution treatment and oil quench. The precipitate volume fraction was 55 ± 3%, determined from both the neutron Rietveld refinement and conventional x-ray measurements. Non-linear stress-strain behavior was observed in tension (but not in compression) and was attributed to reversible stress-induced martensite (SIM) that forms to accommodate the stress as revealed by neutron diffraction measurements. The tensile and compressive neutron data also showed peak broadening and residual lattice strains. Transmission and scanning electron microscopy revealed stress-induced coarsening of Ni4 Ti3 precipitates in both tension and compression tested samples, but precipitation and growth of the stable Ni3 Ti phase was observed only after tensile testing. Finally, the potential ramifications of these microstructural changes are discussed. Highlights: Intermetallic 60NiTi alloy exhibited low modulus, extensive elastic strain capability, and high strength. Non-linear stress-strain behavior in tension was attributed to reversible stress-induced martensite (SIM). Stress-induced coarsening of Ni4 Ti3 precipitates in both tension and compression was observed. Precipitation and growth of the stable Ni3 Ti phase was observed only after tensile testing.